CONCEPT OF CORPORATE INFORMATION SYSTEMS WITH CLOUDING COMPUTING AND ITS INFORMATION SECURITY - U. A. Vishniakou; M. M. Gondag Sas; M. G. Mozdurani Shiraz (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Concept of integration corporate information systems (ICIS) with clouding computing (CC) is represented. Variants such ICIS are shown. Main problems of information security (IS) in CC area and mechanism of authentification are analyzed. Development directions of IS in ICIS with use of intelligent technologies are given. Models of IS in ICIS with use of multi agents technologies are proposed. Concept of architecture building of IS in ICIS and its development on the base of intelligent management and semantic technologies are represented.